2004
DOI: 10.1002/jbm.b.30100
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical factors influencing bacterial transfer from contact lenses to surfaces with different roughness and wettability

Abstract: The aim of this study was to determine the transfer of Pseudomonas aeruginosa No. 3 and Staphylococcus aureus 835 from contact lenses to surfaces with different hydrophobicity and roughness. Bacteria were allowed to adhere to contact lenses (Surevue, PureVision, or Focus Night & Day) by incubating the lenses in a bacterial suspension for 30 min. The contaminated lenses were put on a glass, poly(methylmethacrylate), or silicone rubber substratum, shaped to mimic the eye. After 2 and 16 h, lenses were separated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…9 Thus, the roughness differences between lenses observed here cannot be attributed to the manufacturing procedure. Besides the mode of elaboration, other authors have linked the presence of methacrylic acid (MA) 6 or a reduced water content 24,9 to a greater lens surface roughness.…”
Section: -Discussionmentioning
confidence: 99%
“…9 Thus, the roughness differences between lenses observed here cannot be attributed to the manufacturing procedure. Besides the mode of elaboration, other authors have linked the presence of methacrylic acid (MA) 6 or a reduced water content 24,9 to a greater lens surface roughness.…”
Section: -Discussionmentioning
confidence: 99%
“…It was also previously demonstrated that the surface roughness increase, the biofilm deposited on the lens increase (Baguet et al, 1995), and that bacterial transfer from a CL is determined by the roughness and hydrophobicity of the surface receiving the bacteria (Vermeltfoort et al, 2004). Daily replacement CL in present study are suppose to acquire more deposits during wear as they had the highest increase in roughness values when higher areas are considered.…”
Section: μMmentioning
confidence: 53%
“…The effect of surface roughness on bacterial adhesion to a CL is still far from being well understood. According to prior work, it seems clear that surface roughness is related to deposit formation and microorganism colonization of the surface (Baguet et al, 1995;Vermeltfoort et al, 2004). Greater surface roughness determines a greater specific surface area, thus creating more available active sites for thermodynamic reactions.…”
Section: Effect Of Hydrophobicity and Surface Roughnessmentioning
confidence: 99%
See 2 more Smart Citations